Analysis of Redox Series of Unsymmetrical 1,4-Diamido-9,10-anthraquinone-Bridged Diruthenium Compounds - Mandal, Abhishek; Hoque, Md Asmaul; Grupp, Anita; Paretzki, Alexa; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic chemistry, 2016)
The unsymmetrical diruthenium complexes [(bpy)2Ru(II)(μ-H2L(2-))Ru(III)(acac)2]ClO4 ([3]ClO4), [(pap)2RuII(μ-H2L(2-))Ru(III)(acac)2]ClO4 ([4]ClO4), and [(bpy)2Ru(II)(μ-H2L(2-))Ru(II)(pap)2](ClO4)2 ([5](ClO4)2) have been obtained by way of the mononuclear precursors [(bpy)2Ru(II)(H3L(-))]ClO4 ([1]ClO4) and [(pap)2Ru(II)(H3L(-))]ClO4 ([2]ClO4) (where bpy = 2,2′-bipyridine, pap = 2-phenylazopyridine, acac(-) = 2,4-pentanedionate, and H4L = 1,4-diamino-9,10-anthraquinone). Structural characterization by single-crystal X-ray diffraction and magnetic resonance (nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR)) were used to establish the oxidation state situation in each of the isolated materials. Cyclic voltammetry, EPR, and ultraviolet-visible-near-infrared (UV-vis-NIR) spectroelectrochemistry were used to analyze the multielectron transfer series of the potentially class I mixed-valent dinuclear compounds, considering the redox activities of differently coordinated metals, of the noninnocent bridge and of the terminal ligands. Comparison with symmetrical analogues [L2′Ru(μ-H2L)RuL2′](n) (where L′ = bpy, pap, or acac(-)) shows that the redox processes in the unsymmetrical dinuclear compounds are not averaged, with respect to the corresponding symmetrical systems, because of intramolecular charge rearrangements involving the metals, the noninnocent bridge, and the ancillary ligands.